JOURNAL OF GOVERNMENT & POLITICS : Moving toiwards a Normalised Path: Political Islam in Contemporary Indonesia - Ridho Al-Hamdi (FISIPOL UMY, 2017)
As the largest predominantly Muslim country of the globe, Indonesia nearly achieves two decades of its democratisation wave since the downfall of the Authoritarian Rule in 1998.